Occurrence of cyclo-siloxanes in wastewater treatment plants - quantification and monitoring - Kulkarni, Harshad Vijay, author; Omur-Ozbek, Pinar, advisor; Carlson, Kenneth, committee member; Dooley, Gregory, committee member (Colorado State University. Libraries, 2012)
Siloxanes are persistent, bio-accumulative and toxic emerging contaminants introduced to wastewater from common healthcare and biomedical products, and various industrial processes. They remain unchanged through wastewater treatment and a considerable portion ends up in surface waters through effluent discharge. 30 to 60 ng/L Decamethylcyclopentasiloxane (D5) was detected in two UK Rivers, while ~400 ng/L of D5 may be found in wastewater effluents. Hence, siloxanes are under consideration by Canadian Environmental Assessment Agency and UK Environment Agency for drinking water regulations. Siloxanes are hydrophobic and also accumulate in activated sludge and biogas, causing mechanical problems due to scaling. This research aims: to quantify the siloxanes in sludge samples obtained from Loveland, CO wastewater treatment plant (WWTP); and to study their removal. A method was developed to effectively extract siloxanes from activated sludge samples using liquid extraction followed by quantification with gas chromatography/mass spectrometry. Results for Loveland Wastewater Treatment Plant samples indicated that Octamethylcyclotetrasiloxane (D4) and Decamethylcyclopentasiloxane D5 are present up to 17.11 µg/g dried-sludge. The effectiveness of H2O2 in siloxane removal was investigated. Sludge samples were spiked with D4 and D5 at 12 mg/g and were treated with 1ml, 3ml, and 5ml of 30% H2O2 for 1hr, 2hr, and 3hr reaction time each. Results indicated a 72% reduction in D4 and D5 levels after 3 hrs.
Keywords: cogeneration; wastewater utilities; gas chromatography-mass spectrometry; cyclosiloxanes; biogas